Extensional and compressional faults in the Everest–Lhotse massif, Khumbu Himalaya, Nepal (Geological Society Publishing House, 1999)
Two large-scale north-dipping, low-angle normal faults cut the Everest massif at the top of the High Himalayan slab in Nepal. The upper fault the Qomolangma Detachment, follows the north slope of Everest from above the ‘Yellow Band’ at c. 8500 m on the Southwest Face down to the Rongbuk glacier. On the south side of Everest this fault places unmetamorphosed Ordovician mudstones and limestones above biotite-grade marbles, calc-silicates and greenschists (Everest series pelites). The lower normal fault, the Lhotse Detachment, places greenschist grade calc-silicates and pelites above sillimanite–K-feldspar-grade gneisses (quartz+biotite+garnet+K-feldspar+plagioclase+sillimanite±cordierite assemblages) formed at temperatures above 650°C. Abundant sheet intrusions, sills and dykes of leucogranite containing tourmaline+muscovite±biotite±garnet are restricted to the footwall of the Lhotse Detachment. The mid–upper greenschist grade Everest pelites, some 2000 m thick on the SW face of Everest, form a northward tapering wedge bounded by normal faults below and above. A major compressional fault, the Khumbu Thrust, bounds the base of a c. 3–6 km thick sheet which consists of a series of flat-lying leucogranite sills or sheets extending more than 25 km south of Everest. The leucogranite peaks of Ama Dablam, Kangteiga and Tamserku are all part of the same sheet, which, prior to erosion, was probably originally continuous. The main granite emplacement mechanism was by syn-tectonic magma injection by hydraulic fracture propagation during simple shear, along a series of large sills from their source region at depth to the north. Granite emplacement occurred during upper crustal extension along the top of the High Himalayan slab, although final motion on the Lhotse Detachment post-dated granite emplacement. Both the normal faults at the top of the slab and the Khumbu thrust at the base of the leucogranite sheets were mechanically linked, resulting in the southward extrusion of rocks formed at c. 12–30 km depth within the High Himalayan slab.